Improving the safety relevance of automatic emergency braking testing programs: An examination of common characteristics of police-reported rear-end crashes in the United States. (10th October 2022) - Kidd, David G.
Abstract: Objective: Forward collision warning and automatic emergency braking (AEB) systems help prevent rear-end crashes where a vehicle strikes the rear of another. However, the benefits may be limited if the systems are stymied by common crash circumstances or only target scenarios evaluated in vehicle testing programs. This study examined the prevalence of characteristics that may limit AEB system performance in police-reported rear-end crashes and the relevance of scenarios used to evaluate these systems. Methods: Police-reported rear-end crashes ( n  = 6, 731, 215, Crash Report Sampling System) and fatal rear-end crashes ( n  = 4, 285, Fatality Analysis Reporting System) with a fatality in the striking or struck vehicle during 2016–2019 were analyzed. Percentages of police-reported rear-end crashes, nonfatal-injury rear-end crashes, and fatal rear-end crashes were computed to identify common crash characteristics. Roadway speed limit was used as a proxy for striking vehicle speed. Results: A straight-moving vehicle striking a stopped or decelerating vehicle on roads with a speed limit of 40 km/h (25 mph) or less only accounted for 3% of all rear-end crashes, 3% of nonfatal-injury rear-end crashes, and 1% of fatal rear-end crashes. In contrast, 36% of all rear-end crashes, 36% of nonfatal-injury rear-end crashes, and 11% of fatal rear-end crashes involved a straight-moving vehicle striking a stopped or decelerating vehicle on roads with a speed limit between 56 and 72 km/h (35 and 45 mph). A medium or heavy truck was the struck vehicle in 32% of fatal rear-end crashes, and a motorcycle was the struck vehicle in 11% of fatal rear-end crashes. At least one of the following characteristics that may degrade AEB system performance was present in 14% of the rear-end crashes studied: striking vehicle turning; a struck vehicle turning or changing lanes; a struck vehicle that is not a passenger vehicle; wintery weather; wet or icy roads; or a speed limit of 113 km/h (70 mph) or higher. Conclusion: Circumstances shown to diminish AEB effectiveness accounted for 14% of rear-end crashes, and scenarios currently used to evaluate AEB systems accounted for 3%. Evaluating AEB systems at speeds up to 72 km/h (45 mph) and incorporating a motorcycle or medium/heavy truck target will make AEB evaluations more representative of police-reported rear-end crashes.